Mapping the Pathways: Understanding the Interplay between Research Attitudes and Investigative Skills in Postgraduate Students in Peru - Meneses-La-Riva, Monica Elisa; Ocupa-Cabrera, Hitler Giovanni; Calvo-Gastañaduy, Carola Claudia; Suyo-Vega, Josefina Amanda; Fernández-Bedoya, Víctor Hugo (Journal of Education Culture and Society, 2025)
Aim. Research attitudes and investigative skills are currently recognised as vital factors for student success in both their academic and professional development, particularly in decision-making. Fostering positive research attitudes and enhancing investigative skills play a pivotal role in bolstering students’ academic performance. The primary aim of this study was to investigate the relationship between research attitudes and investigative skills among postgraduate university students. Methods. We conducted a quantitative, basic, descriptive-correlational, cross-sectional, non-experimental study. Our sample comprised 80 master’s students in the field of education, selected through a non-probabilistic convenience sampling method in Peru. We employed two validated instruments for data collection: one assessed research attitudes across three dimensions (research disinterest, research vocation, and research valuation), and the other measured investigative competency with two dimensions (methodological skills and generic skills). The instruments demonstrated high reliability, with respective values of 0.88 and 0.81. Results. Our findings revealed a moderate correlation between the variables investigated, indicated by a Spearman’s Rho coefficient of 0.595, which was statistically significant at a bilateral level of 0.01. Specifically, we observed correlations of 0.624 in the dimension of research disinterest, 0.569 in research vocation, and 0.538 in research valuation. Conclusion. The study demonstrates a significant and meaningful link between the dimensions of research attitudes and investigative skills in university students. This underscores the importance of nurturing positive research attitudes and enhancing investigative skills in the context of postgraduate education